2020
DOI: 10.1136/annrheumdis-2020-218704
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence to: ‘Combination of human umbilical cord mesenchymal (stromal) stem cell transplantation with IFN-γ treatment synergistically improves the clinical outcomes of patients with rheumatoid arthritis’

Abstract: Patient and public involvement Patients and/or the public were not involved in the design, or conduct, or reporting, or dissemination plans of this research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Epidemiological data has revealed that pSS prevalence is approximately 1% of general population and female predominance (16:1) ( 2 ). Genetic inheritance and environmental factors are previously reported to enhance pSS pathogenesis; however, pSS etiology remains unclear, for which viral infection has been as well considered an external factor for it induces chronic inflammation ( 3 , 4 ). Viral particles translated by viral gene would act as autoantigens, which attract auto-antibodies to combine and trigger proliferation of B cells to cause autoimmune disease.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological data has revealed that pSS prevalence is approximately 1% of general population and female predominance (16:1) ( 2 ). Genetic inheritance and environmental factors are previously reported to enhance pSS pathogenesis; however, pSS etiology remains unclear, for which viral infection has been as well considered an external factor for it induces chronic inflammation ( 3 , 4 ). Viral particles translated by viral gene would act as autoantigens, which attract auto-antibodies to combine and trigger proliferation of B cells to cause autoimmune disease.…”
Section: Introductionmentioning
confidence: 99%
“…Immunotherapy, which could be traced back to the late 19th century [69], has emerged as a promising treatment of cancer cells as well as infectious diseases [52,70]. For instance, cellular therapies from donor lymphocyte infusion are utilized to treat cancer relapse following allogeneic hematopoietic stem cell transplantation to bring about graft-vs-leukemia reaction [71][72][73], where antigen-experienced T cells would recognize pathogens such as cytomegalovirus or Epstein-Barr virus. Likewise, antigen-specific T cells acquired by cell expansion or genetically engineered pathogen-specific Tc clones have been applied to infectious diseases [74,75].…”
Section: Discussionmentioning
confidence: 99%
“…The authors declare no conflicts of interest. Kevin Sheng-Kai Ma 1,2 Chien-Te Liu 3 Wei-Chiao Kao 3 Yung-Heng Lee…”
Section: Co N Fli C T S O F I Nte R E S Tmentioning
confidence: 99%